ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN PRODUK KOSMETIK WARDAH DI KOTA SEMARANG - Amalia Octavanda, 14.05.51.0119; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the influence of brand image, product quality, customer satisfaction on customer loyalty at customer wardah cosmetics in Semarang City.The population in this study is customer of wardah cosmetics in Semarang City. and got 100 respondent sampling. Based on the analysis can be concluded that there is significant effect of brand image variable to customer loyalty, and significant affect of product quality variable to customer loyalty. There is significant effect of customer satisfaction variable of customer loyalty. The result of the research shows that the ability of the model to explain correctly the effect of brand image, product quality, and customer satisfaction is 54,0% on customer loyalty. While the other by 46,0% influenced by other variable. Keywords : brand image, product quality, customer satisfaction and customer loyalty